2014
DOI: 10.1507/endocrj.ej13-0277
|View full text |Cite
|
Sign up to set email alerts
|

Plasma free metanephrines in the diagnosis of pheochromocytoma: diagnostic accuracy and strategies for Japanese patients

Abstract: abstract. Measuring the levels of the plasma free metanephrines (PFMs) represents a recently developed and promising test for the diagnosis of pheochromocytoma in the United States and Europe. As this test has not yet been evaluated in Japan, it is necessary to evaluate the diagnostic efficacy of measuring the levels of PFMs compared with the standard measurement of the urinary excretion of metanephrines (uMNs) whose reliability is well established to detect of pheochromocytoma. A total of 101 Japanese subject… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
3
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(4 citation statements)
references
References 10 publications
(27 reference statements)
1
3
0
Order By: Relevance
“…In our study, specificity of measurements of plasma-free MNs exceeded that of the 24 urinary-fractionated MNs and does not support their contention. Our findings are in line with some [ 17 , 38 , 39 , 40 , 41 , 42 ] but not all [ 30 , 43 , 44 ] authors assessing the performance of P-MNs measured by EIA, and is not related to sample size nor to pre-TP of PPGL of the study populations ( Supplementary Figures S2 and S4 , respectively). Supplementary Figure S3 gives a summary of the diagnostic performance of the EIAs of the available literature for the quantification of plasma-free metanephrines.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…In our study, specificity of measurements of plasma-free MNs exceeded that of the 24 urinary-fractionated MNs and does not support their contention. Our findings are in line with some [ 17 , 38 , 39 , 40 , 41 , 42 ] but not all [ 30 , 43 , 44 ] authors assessing the performance of P-MNs measured by EIA, and is not related to sample size nor to pre-TP of PPGL of the study populations ( Supplementary Figures S2 and S4 , respectively). Supplementary Figure S3 gives a summary of the diagnostic performance of the EIAs of the available literature for the quantification of plasma-free metanephrines.…”
Section: Discussionsupporting
confidence: 91%
“…However, PPGL not discovered are potentially life-threatening [ 12 , 13 , 48 ], and suspicion of PPGL given a positive biochemical test result may always be prudent. Six of the pertinent studies assessing P-MNs by EIA in comparison to other methods do not mention a FU of their patients defined free of PPGL [ 30 , 40 , 42 , 43 , 44 ], or do not report the duration of FU [ 38 ]. Three other series provide clinical, or clinical and radiological FU for 1–2 years [ 17 , 38 , 41 ] which is in line with our approach ( Supplementary Figure S4 ).…”
Section: Discussionmentioning
confidence: 99%
“…Whether this requirement is feasible for every patient at every center remains questionable. The clinical utility of plasma free metanephrines as a diagnostic for pheochromocytomas in Asian patients was lately evaluated by Tanaka et al [12], but the plasma free metanephrines were determined using an enzyme immunoassay. Unfortunately, such procedures can be susceptible to non-specific binding and cross-reactivity leading to lower diagnostic sensitivity and specificity compared to the liquid chromatography-tandem mass spectrometry (LC-MS/MS) which is known a reliable and sensitive test for the biochemical detection of pheochromocytoma [13].…”
Section: Discussionmentioning
confidence: 99%
“…33 Several studies have demonstrated that plasma and urinary O-methylated catecholamine metabolites, normetadrenaline (NMA) and metadrenaline (MA) have high diagnostic sensitivity and specificity, which is essential for the biochemical diagnosis of PPGL (Table 2). [34][35][36][37][38][39][40][41][42][43][44][45][46][47][48][49][50][51][52][53] While there have been differences observed in the diagnostic sensitivity and specificity of UMets and PMets using different analytical methodologies, to date, there has not been a multicentre comparison using the gold standard method 1 of liquid chromatography tandem mass spectrometry (LC-MS/MS) for analysis.…”
Section: Biochemical Screeningmentioning
confidence: 99%